The consolidation of emulsion templating and thiol-ene click chemistry as a route to degradable polyhipes for biomedical applications - Hobiger, Viola (visokošolska dela, 2022)
Thiol-ene click chemistry has been on the rise for the past two decades. In the past years, it has also found its way into the synthesis of porous polymers from emulsion templating (polyHIPEs) due to its versatility and convenience. It is an especially attractive pathway for scaffolds intended for biomedical purposes since the resulting materials are often biocompatible and degradable due to hydrolyzable ester bonds introduced via the thiol monomers. The overall aim of this dissertation was to bring thiol-ene click chemistry with a focus on photopolymerization to the forefront of polyHIPE research, highlighting the great potential in combining the preparation technique of emulsion templating together with thiol-ene click chemistry. A study to understand the mechanisms of emulsion stability with a focus on already established thiol-ene formulations was conducted. It was possible to study and synthesize materials with a bicontinuous pore morphology within this project. Compared to the typical cellular pore morphology of a polyHIPE, a bicontinuous structure could be especially useful for separation applications. Furthermore, it was possible to induce a phase inversion, leading to small polymer particles.One part of the dissertation focused on synthesizing hydrophilic polyHIPEs from poly(ethylene glycol) monomers and a hydrophilic thiol through an oil-in-water high internal phase emulsion. The resulting materials exhibited high porosity and small average pore diameters of 2.2 µm. Water uptake and degradation studies were performed. The potential of the material for drug release was demonstrated with the chosen model drug salicylic acid.Furthermore, a HIPE formulation based on the acrylate 1,6-hexanediol diacrylate and thiol tris(3-mercaptopropionyloxy)-ethyl-isocyanurate was developed. For the developed poly(acrylate-co-thiol) polyHIPEs, the effect of oxidation thioethers present in the polymer network on the material properties was explored. This investigation was performed firstly to tune material properties, e.g. increase the glass transition temperature and tensile strength, and secondly, to highlight the oxidation properties of thioether-containing polymer networks. The oxidation responsiveness should be considered when a biomedical application is envisioned since inflammatory processes lead to oxidative stress in an organism. The formulation was also investigated for its additive manufacturing potential. The emulsion composition had to be adjusted to obtain a printable emulsion. Furthermore, it was possible to exclude harmful solvents, making the overall printing process more environmentally friendly and less hazardous for operators.A polyHIPE from the biobased vinyl ester O,O‘-(hexahydrofuro3,2-bfuran-3,6-diyl) divinyl diadipate (GDVA), which was especially promising as a biocompatible and biodegradable scaffold for tissue engineering, was prepared together with different thiol chain-transfer agents. The synthesis of cellular interconnected polyHIPEs from these starting materials proved challenging. However, the first synthesis of a biobased vinyl ester polyHIPE could be reported.A final project was conducted in collaboration with Lithoz GmbH. In collaboration, it was possible to establish the first 3D printed ceramics from high internal phase emulsion precursors. For this purpose, trimethylolpropantriacrylte and the thiol trimethylolpropane tris(3-mercaptopropionate) were employed as monomers together with alumina particles to form a composite polyHIPE which would then be submitted to sintering, resulting in an intrinsically porous printed ceramic, allowing for high customization and complex porous morphologies.
Keywords: additive manufacturing; doktorske disertacije; fotopolimerizacija; photopolymerization; poliHIPE; polyHIPE; proizvodnja aditivov; thiol-ene; tiol-en